Preparation and characterization of polyamide 12 composites for craniofacial reconstruction utilizing additive manufacturing - Abdullah, Abdul Manaf (2016)
This study was carried out to prepare and characterize polyamide 12 composites as potential biomaterial for craniofacial reconstruction utilizing additive manufacturing. Polyamide 12 was compounded with ceramic fillers of β-TCP (ranged from 5 to 25 wt%) and zirconia (fixed at 15 wt%) via twin screw extruder. Obtained pellets were used to characterize the thermal properties, melt flow rate and chemical bonding of the composites. The remaining pellets were used to prepare tensile, flexural and impact specimens via injection molding and 3D printing. The mechanical and topological properties of prepared specimens were evaluated and analyzed using statistical analysis of One-Way ANOVA with significant level of p=0.05. The melt flow rate of the polyamide 12 composites were significantly difference as compared to pure polyamide (p<0.01). Mechanical and topological properties of injection molded polyamide 12 composites showed a mix of significant and insignificant differences as compared to pure polyamide. However, no significant differences were detected in the mechanical and topological properties of 3D printed composites. The mechanical properties of 3D printed polyamide 12 composites was influenced by inter layer bonding which could be boosted further via optimization of bed temperature. Overall, with mechanical and topological properties that could be enhanced, polyamide 12composites are potential biomaterial for craniofacial reconstruction.